2015
DOI: 10.1111/bjd.14032
|View full text |Cite
|
Sign up to set email alerts
|

Risk of depression in women with psoriasis: a cohort study

Abstract: Summary Background Psoriasis is a common, chronic and inflammatory disease of the skin, which has been associated with depression in cross-sectional studies with limited adjustment for confounders. Objectives In this prospective cohort study, we investigated the risk of incident depression among individuals with psoriasis and psoriatic arthritis (PsA). Methods We included 50 750 US female nurses from the Nurses’ Health Study who were free of depression at baseline in 2000. Those participants who had ever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 31 publications
7
58
1
8
Order By: Relevance
“…122 The risk of depression was greatest among patients receiving therapies for severe psoriasis (HR 1.72; 95% CI 1.57–1.88). Similarly, a study of women in the Nurses’ Health Study 123 found psoriasis to be associated with a nearly 30% increased risk of depression (RR 1.29; 95% CI 1.10–1.52), independent of age, BMI, lifestyle factors, and comorbid conditions.…”
Section: Mood Disordersmentioning
confidence: 91%
“…122 The risk of depression was greatest among patients receiving therapies for severe psoriasis (HR 1.72; 95% CI 1.57–1.88). Similarly, a study of women in the Nurses’ Health Study 123 found psoriasis to be associated with a nearly 30% increased risk of depression (RR 1.29; 95% CI 1.10–1.52), independent of age, BMI, lifestyle factors, and comorbid conditions.…”
Section: Mood Disordersmentioning
confidence: 91%
“…More than 40% meet criteria for probable mood disorders [36] and the prevalence of depression and/or anxiety disorder ranges between 30% [37] and 58% [38]. Moreover, a diagnosis of psoriatic arthritis further increases the likelihood of depression [39,40]. A couple of recent reports on the relation between psoriasis and psoriatic arthritis and risk of depression in the US showed that psoriasis was significantly associated with major depression, even after adjustment for sex, age, race and co-morbidities, but that disease severity was not found co-related with increased risk [40,41].…”
Section: Depression and Psoriasismentioning
confidence: 99%
“…Depression seen in half of the patients may affect the quality of life quite negatively [7,9]. In a study with a very large sample, depression risk in women with psoriasis has been found to be higher than those without psoriasis [4]. In a recent study, the quality of life of 3971 patients with psoriasis has been assessed with EuroQol-5 Dimension Questionnaire (EQ-5D).…”
Section: Dear Editormentioning
confidence: 99%
“…In the study of Dommasch et al, individuals diagnosed with depression or receiving antidepressant treatment have been excluded from the study [4]. In addition, in the study of Hawro et al, it would have been better to exclude those diagnosed with depression or receiving antidepressant treatment from the study.…”
Section: Dear Editormentioning
confidence: 99%